Pengaruh Literasi Keuangan Syariah dan Persepsi Kemudahan Pengguna Terhadap Keputusan Menggunakan Mobile Banking Syariah di Kecamatan Majalengka - Rahayu, Sri; Aziz, Abdul; Setiowati, Nur Eka (Jurnal Keuangan dan Perbankan Syariah, 2025)
Purpose: This study aims to analyze and measure the effect of Islamic financial literacy and perceived user convenience on decisions to use Islamic mobile banking. Design/methodology/approach: The research method used in this research is quantitative with data collection techniques through a google form questionnaire. The sampling technique used was Non Probability Sampling with Purposive Sampling type with 103 respondents. The population is the people of Majalengka District. The data analysis used is the research instrument test, classical assumption test, and hypothesis testing. Research Findings: The results showed that Islamic financial literacy (X1) had no significant effect while perceived user convenience (X2) had a significant effect on the decision to use Islamic mobile banking in Majalengka District (Y),. Simultaneously, X1 and X2 have a significant effect on Y with a contribution of 79.8%, the remaining 20.2% is influenced by other factors outside this study. Contribution/Originality/Novelty: The results show that perceived convenience is more dominant than financial literacy, making a strategic contribution to the development of Islamic banking services. Keywords: Literacy, Convenience, Mobile Banking